Association between serum homocysteine level and unexplained infertility in in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI): A retrospective, hospital‐based, case‐control study. Issue 5 (25th December 2019) - Liu, Linli; Lin, Zhou; Lin, Peihong; Jiang, Zhongqing
Abstract: Background: Lower serum homocysteine (Hcy) levels are found to correlate with a better chance of clinical pregnancy and better embryo grades in assisted reproductive technology (ART). However, there is little knowledge on the association between Hcy level and unexplained infertility until now. Methods: A total of 388 infertile women undergoing IVF/ICSI treatments were recruited, including 129 women with unexplained causes (case group) and 259 women with known causes (control group), and the case group was further divided into subgroups A (≤8 μmol/L), B (>8 and <15 μmol/L), and C (≥15 μmol/L) based on the serum Hcy level. The associations between serum Hcy level and IVF/ICSI pregnancy outcomes were examined in infertile women with unknown causes. Results: A significantly higher serum Hcy level was measured in the case group than in the control group ( P  = .008). Subgroup analysis revealed a significant difference in the total number of oocytes retrieved among subgroups A, B, and C ( P  = .031), and no significant difference was seen among these three groups in terms of age, BMI, E2 level on the hCG day, number of M‐II oocytes, number of fertilized oocytes, or total number of high‐quality embryos ( P  > .05). Spearman correlation analysis revealed a negative correlation between serum Hcy level and total number of oocytes retrieved ( r  = −.406, P  = .019). Univariate and multivariate linear regression analyses revealed that serum Hcy level had no correlations with any IVF/ICSI outcomes. Conclusion: Serum Hcy level has no associations with IVF/ICSI pregnancy outcomes.